Uji Penghambatan Aktivitas alfa-glukosidase Ekstrak dan Fraksi Daun Antidesma neurocarpum Miq. - Widihasputri, Rieka; Elya, Berna; Azizahwati, Azizahwati (Majalah Ilmu Kefarmasian, 2012)
Diabetes mellitus is a metabolic dysfunction disease showed by hyperglicemia and abnormality of carbohydrates, fats, and proteins metabolism. It is known can be cured with a-glucosidase inhibitor. Previous experiment reported that methanol extract from leaves of Antidesma neurocarpum Miq. has a strong inhibitory activity of a-glucosidase (IC50 = 2,18 mikrogram/mL). The aim of this experiment was to know about the most active extract and fraction of inhibitory activity of a-glycosidase and also the chemical compounds from those most active extract and fraction. Extraction is done by using multilevel maceration (n-hexane, ethyl acetate and methanol). Inhibitory activity of a-glucosidase tested with microplate reader at 405 nm wavelength. As standard, we used carbose (IC50=38.37 gg/mL). Methanol extract has the strongest inhibitory activity of a-glucosidase as shown the highest inhibitor percentage (89.53%). It is identified the chemical compounds and fracinationed by flash column chromatography. Fractination produced 15 combined fractions. Combined fractions which more than 200 mg tested to know their inhibitory activity of a-glucosidase. Result showed that the most active fraction is the 8th (IC50=40.77 gg/mL) with a competitive inhibitor mechanism to a-glycosidase. Chemical compounds that is found in the methanol extract and 8th fraction of Antidesma neurocarpum Miq. leaves are flavonoids, tannins, glycosides, fenol and alkaloids.